2013
DOI: 10.1155/2013/435154
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pectinolytic Enzymes by the Yeast Wickerhanomyces anomalus Isolated from Citrus Fruits Peels

Abstract: Wickerhamomyces anomalus is pectinolytic yeast isolated from citrus fruits peels in the province of Misiones, Argentine. In the present work, enzymes produced by this yeast strain were characterized, and polygalacturonase physicochemical properties were determined in order to evaluate the application of the supernatant in the maceration of potato tissues. W. anomalus was able to produce PG in liquid medium containing glucose and citrus pectin, whose mode of action was mainly of endo type. The supernatant did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
1
19
0
7
Order By: Relevance
“…Similar results were found for pectinases produced by K. marxianus (Schwan et al 1997), K. marxianus CCT 3172, and Pichia anomala S16 (Masoud and Jespersen 2006) exhibited maximum activity at 40°C. Pectinases produced by S. paradoxus (Eschstruth and Divol 2011) exhibited maximum activity at 45°C and that of K. wickerhamii (Moyo et al 2003), P. kluyveri S13Y4 (Masoud and Jespersen 2006) and Wickerhanomyces anomalus (Martos et al 2013) at 50°C. The profiles of pectinase activity at different temperatures over time (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found for pectinases produced by K. marxianus (Schwan et al 1997), K. marxianus CCT 3172, and Pichia anomala S16 (Masoud and Jespersen 2006) exhibited maximum activity at 40°C. Pectinases produced by S. paradoxus (Eschstruth and Divol 2011) exhibited maximum activity at 45°C and that of K. wickerhamii (Moyo et al 2003), P. kluyveri S13Y4 (Masoud and Jespersen 2006) and Wickerhanomyces anomalus (Martos et al 2013) at 50°C. The profiles of pectinase activity at different temperatures over time (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). Estos bajos valores de pH alcanzados, podrían, de prolongarse el cultivo, afectar la estabilidad de la enzima PG, ya que en estudios previos se determinó que la enzima permanece estable en un rango de pH entre 3,0 a 6,0 (Martos et al, 2013b).…”
Section: Resultados Y Discusiónunclassified
“…Esta enzima es de gran importancia industrial ya que posee actividad protopectinasas (PPasa) o capacidad macerante de tejidos vegetales (papa, mandioca, zanahoria, etc.) (Martos et al, 2013a, Martos et al, 2013b. La potencial aplicación industrial de esta enzima justifica la realización de estudios relacionados con su producción a mayor escala.…”
Section: Introductionunclassified
“…Some authors reported that during the purification procedure, some protein stabilizing factors might be lost (Naidu and Panda 2003;Martins et al 2007;Pedrolli and Carmona 2010). Data published previously with crude PG from W. anomalus obtained in YNB medium showed that enzyme maintained 78% of its residual activity of after 30 min at 55ºC (Martos et al 2013b). These results suggested that PG lost stability after the purification process.…”
Section: Thermal Stability Of Pgmentioning
confidence: 99%